Simultaneous synthesis and characterization of in/out-isomers of disilabicyclo[14.14.14]alkanes. Issue 63 (19th July 2021) - Ikeda, Yuto; Inagaki, Yusuke; Setaka, Wataru
Abstract : Facile and simultaneous synthesis of diphenyldisilabicyclo[14.14.14]alkane in/out -isomers was achieved by using organosilicon chemistry. Only two diastereomers were isolated due to homeotropic isomerizations. Abstract : Facile and simultaneous synthesis of diphenyl-disilabicyclo[14.14.14]alkane in/out -isomers was achieved by using organosilicon chemistry. Although the formation of several in/out -isomers would be conceivable, only two diastereomers, i.e. the ( traditional -)out, out -isomer and the twist-out, out -isomer, could be isolated because of homeomorphic isomerization. Crystal structures of the diastereomers were confirmed.